Get an eyeful of this: a new species of giant spitting cobra from eastern and north-eastern Africa (Squamata: Serpentes: Elapidae: Naja) - Wüster, Wolfgang; Broadley, Donald G. (Zootaxa, 2007)
We describe a new species of giant spitting cobra, Naja ashei sp. nov., from eastern and north-eastern Africa. The species was previously regarded as a colour phase of the black-necked spitting cobra, N. nigricollis. However, mtDNA sequence data show it to be more closely related to N. mossambica than N. nigricollis. The new species is diagnosable from all other African spitting cobras by the possession of a unique clade of mtDNA haplotypes and a combination of colour pattern and scalation characteristics. Its distribution includes the dry lowlands of northern and eastern Kenya, north-eastern Uganda, southern Ethiopia and southern Somalia.